EU: China and the Non-transparent Race for Inward FDI - Lars Oxelheim; Pervez Ghauri (Research Institute of Industrial Economics (IFN), 2008)
In this paper it is argued that the restructuring following the stiffer competition stemming from increased global integration will trigger a race between countries to attract inward foreign direct investment (FDI). It is further argued that this race consists of last minute efforts and tailor-made packages designed by governments and their agencies to temporarily improve their countrys otherwise inferior profile. This race is non-transparent and the factors used to compete for inward FDI (the 'elements' of the race) deviate from those of long-term efforts to develop a favourable investment climate and improve productivity, as well as medium-term efforts, such as lowering corporate taxes. The paper elaborates on the research problem of properly understanding the drivers of inward FDI in the absence of data on the elements of the non-transparent race. It also addresses the economic policy problem following from this race with a scenario where a large share of global FDI ends up in China, putting the cohesion of the EU at stake and triggering a regional race within China.
Keywords: E61; F15; F21; F23; F36; F42; G18; G34; 330; Inward FDI; China; European Union; Investment-diverting Policies; Direktinvestition; Multinationales Unternehmen; Investitionspolitik; China; EU-Staaten